(untitled) (Al-Aasar, 2025)
Background: Sacroiliac joint dysfunction (SIJD) is a common cause of lower back pain, significantly impacting daily activities and quality of life. Various treatment approaches, including mobilization and high-velocity low-amplitude (HVLA) thrust manipulation, have been explored to manage SIJD. Objective: This study aimed to compare the effectiveness of sacroiliac joint mobilization and HVLA thrust manipulation in reducing pain and functional disability in female patients with SIJD. Methodology: A single-blinded randomized controlled trial (RCT) was conducted with 72 female participants aged 25–50 years. Participants were randomly assigned to two groups: Group 1 received sacroiliac joint mobilization, while Group 2 received HVLA thrust manipulation. Both groups underwent treatment three times per week for four weeks. Pain intensity and functional disability were assessed using the Numeric Pain Rating Scale (NPRS) and Modified Oswestry Disability Index (MODI), respectively. Statistical analysis was performed using SPSS 20.0. Results: Both interventions significantly reduced pain and improved functional status (p < 0.05). NPRS scores decreased significantly across all assessment weeks in both groups, with comparable improvements in MODI scores. Conclusion: Both mobilization and HVLA thrust manipulation are effective in reducing pain and disability in female patients with SIJD. Further research with larger sample sizes is recommended.